First Case Report of Arrhythmogenic Right Ventricular Cardiomyopathy Showing Refractory Ventricular Tachycardia Induced by Thyroid Storm due to Graves’ Disease - Masaki Matsubara; Tomohiro Tanaka; Akinori Wakamiya; Tamiko Tamanaha; Hisashi Makino; Tomonori Tanei; Takeshi Aiba; Kengo Kusano; Kiminori Hosoda (Case Reports in Endocrinology)
A 48-year-old man who was diagnosed with arrhythmogenic right ventricular cardiomyopathy (ARVC) due to a plakophilin 2 gene mutation developed acute both-sided heart failure with rapid atrial fibrillation and was hospitalized. After admission, sustained ventricular tachycardia, which was refractory to antiarrhythmic agents, occurred repeatedly, and required electrical cardioversion. He was diagnosed with thyroid storm due to Graves’ disease, and treatment for hyperthyroidism was initiated. After the treatment, lethal arrhythmia did not reoccur, and biventricular heart failure ameliorated. To our best knowledge, this is the first report in English of a patient with ARVC showing refractory arrhythmia induced by thyroid storm due to Graves’ disease.